Актуальні питання юридичної науки та практики. Вип. 3 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2023)
У збірнику наукових праць вміщено статті за матеріалами інтернет-конференції студентів та молодих вчених "Актуальні питання юридичної науки та практики". Авторами статей розкрито ряд актуальних питань різних галузей права України, особливості інститутів права у період політичного режиму воєнного стану. The collection of scientific works contains articles based on the materials of the Internet conference of students and young scientists "Current Issues in Legal Science and Practice". The authors of the articles revealed a number of current issues in various branches of Ukrainian law, the peculiarities of legal institutions during the period of the political regime of martial law.